Suscetibilidade relativa dos girinos de Uperodon taprobanicus (Anura: Microhylidae) e Duttaphrynus melanostictus (Anura: Bufonidae) aos girinos predadores de Hoplobatrachus tigerinus (Anura: Dicroglossidae): importância dos refúgios e da velocidade de nat - Mogali, Santosh M.; Shanbhag, Bhagyashri A.; Saidapur, Srinivas K. (Phyllomedusa: Journal of Herpetology, 2023)
The relative susceptibility of two closely associated herbivorous tadpole species (Uperodon taprobanicus and Duttaphrynus melanostictus) to their natural carnivorous predatory tadpole, Hoplobatrachus tigerinus and the significance of refugia in predator avoidance was studied in the laboratory. In a total of 50 trials, 10 tadpoles each of U. taprobanicus and D. melanostictus of comparable sizes were exposed to starved H. tigerinus. Twenty-five trials included refugia while 25 did not. The results of this study showed that in both the presence and absence of refugia, D. melanostictus tadpoles fell prey to H. tigerinus more frequently than U. taprobanicus tadpoles. A key difference between the two prey species is the speed of swimming; Vmax of D. melanostictus (13.58 cm/s) tadpoles is significantly lower than that of U. taprobanicus (24.89 cm/s) tadpoles. This is likely to be the main reason why more D. melanostictus tadpoles were preyed upon than were U. taprobanicus tadpoles. It is important to note that the Vmax of the predator (60.21 cm/s) is much greater than those of the two prey species. However, predation risk of both prey tadpole species was affected significantly by the presence of refugia. The susceptibility of both prey tadpole species was lower where refugia were available. The present study clearly demonstrates that the more efficient avoidance of predation by U. taprobanicus tadpoles could be due to better use of refugia and their faster rate of movement.